Institutional Reform of Islamic Education in the Context of Religious Moderation: A Literature Review on Policy Direction of the Ministry of Religious Affairs - Azis, Annisa Rahmania; Tamimi, Abdillah Rosyid (Badan Riset dan Inovasi Daerah Provinsi Jawa Timur, 2025)
This study is motivated by the misalignment between religious-moderation regulations and the institutional readiness of Islamic educational settings, resulting in moderation values remaining largely normative. The research problem focuses on how national policy frameworks—particularly PMA No. 18/2020, KMA No. 93/2022, and Presidential Regulation No. 58/2023—inform the need for institutional redesign within Islamic education. The study aims to map the relationship between regulatory mandates and the structural requirements of Islamic educational institutions. A literature-review method was employed using thematic analysis of regulatory documents, empirical studies, and institutional theory. The results indicate that Islamic educational institutions require transformation in three areas: integrating moderation values into the curriculum, strengthening teacher competence, and reformulating governance systems using moderation-based indicators. These findings underscore the need for a comprehensive institutional redesign model to ensure that moderation values are internalized systemically rather than implemented merely as programmatic initiatives